"I'm concerned – What Do I Do?" recognition and management of disordered eating in fitness center settings. Issue 4 (9th May 2014) - Bratland‐Sanda, Solfrid; Sundgot‐Borgen, Jorunn
ABSTRACT Objective To examine group fitness instructors' knowledge and attitudes toward identification and management of disordered eating (DE). Method Group fitness instructors representing the three largest fitness center companies in Norway (n = 837, response rate: 57%) completed a questionnaire through Questback (www.questback.com). The questionnaire contained items regarding gender, age, educational background, exercise behavior, and knowledge of recognition and response to DE. Results Eighty‐nine percent of the respondents reported knowledge about symptoms of DE, 29% was classified with adequate DE knowledge skills. Forty‐nine percent of the instructors reported current concern about DE among one or more members, 47% reported knowledge about how to recognize and respond to DE, and 37% reported knowledge about their fitness center's guidelines for approaching DE concerns. The level of formal education in sports and exercise, and a history of self‐reported eating disorder, but not fitness instructor experience, were explanatory factors for knowledge about DE symptoms. Both exercise specific educational level and instructor experience were explanatory variables for knowledge about recognition of and response to DE concerns. Discussion Implications of the findings include a need for increased confidence among group fitness instructors regarding how to approach DE concerns, increased awareness of excessive/compulsive exercise as a symptom of DE, and enhanced dissemination of existing guidelines for managing DE concerns among members and/or staff. © 2014 Wiley Periodicals, Inc. (Int J Eat Disord 2015; 48:415–423)